Sex education for adolescents: Indonesian nurse educators' experience as parents - Salim Alvin; Tambunan Evelyn Hemme (Sciendo, 2022)
Sex education toward adolescent remains the most controversial subject due to the various thoughts and ideas of different values present in society. Nurse educators as parents must exemplify sex education to their children. The aim of this present study was to explore parents' experience, with nurse educators background to be exact, on how they convey sex education to their children.